EFL STUDENTS’ EFFORTS FOR ENGLISH PROFICIENCY IMPROVEMENT - Abargiel, Kauna Bismie; Rosyidah, Umniyah Juman (IJEE (Indonesian Journal of English Education), 2024)
Pursuing an English major requires students to master English. However, some variations of English proficiency levels are found. Recognizing how students behave to improve their English as an English department student is needed to profoundly appropriate treatment for students. Therefore, this research aims to explore the EFL students’ efforts to enhance their English proficiency and the differences that may occur between cohorts using mixed methods. The subject of this research is English department students in Malang with 35 students. With survey and interview, this research found that the levels of students’ efforts are: (1) Seldom (Non-compliance level); (2) Often (Procedural effort level); (3) Sometimes (Substantive effort level); and (4) Often (Focal effort level). In addition, the mean effort level of the 2020 cohort is 48, the 2021 cohort is 49.3, the 2022 cohort is 50.17, and the 2023 cohort is 52.75. It can be concluded that the younger their cohort, the higher their effort to improve their English proficiency. Due to the limitation of this study, further studies need to explore the students’ effort in each English skill: speaking, reading, listening, and writing.